The Role of Smart Contracts in Enhancing Mudharabah Contracts in Islamic Finance - Zulfikri, Zulfikri; Hawariyuni, Weni; Nurlia, Nurlia (Universitas Muhammadiyah Pontianak, 2023)
Islamic finance principles emphasize fairness, transparency, and risk-sharing in financial transactions, with Mudharabah contracts being a prominent embodiment of these principles. This research explores the transformative potential of blockchain-based smart contracts in Mudharabah arrangements. Smart contracts offer automated, transparent, and Shariah-compliant execution of Mudharabah agreements, addressing traditional challenges such as information asymmetry, moral hazard, and trust issues. By enabling real-time profit and loss sharing, risk management, and streamlined dispute resolution, smart contracts enhance the efficacy and trustworthiness of Mudharabah partnerships. The objective of this study is to examine the potential of Smart contracts in addressing the limitations and enhancing the Mudharaba contract, with the intention of its potential application by Islamic financial institutions. The findings show that the application of smart contracts has the potential to significantly enhance the technological, operational, and Sharia compliance aspects of the Mudharaba contract.